QUALITY ANALYSIS OF FINANCIAL REPORT DISCLOSURE ON LOCAL GOVERNMENT WEBSITES (STUDY OF REGENCY/CITY GOVERNMENTS IN CENTRAL SULAWESI PROVINCE 2022-2024) - Fitriyani Aziz Panape; Muhammad Din; Masruddin Masruddin; Rahayu Indriasari (Universitas Tulungagung, 2026)
This study aims to analyze the influence of transparency, accountability, accessibility, and population on the quality of financial report disclosure on the websites of district/city governments in Central Sulawesi Province for the period 2022–2024. The study used a quantitative approach with secondary data obtained from the official websites of the local governments. The sampling technique used a purposive sampling method, resulting in 12 local governments with a total of 33 observations. Data analysis was performed using Partial Least Squares-based Structural Equation Modeling (PLS-SEM) with the assistance of WarpPLS 7.0 software. The results show that transparency, accountability, and accessibility have a positive and significant effect on the quality of local government financial report disclosure. Meanwhile, population has a positive but insignificant effect on the quality of local government financial report disclosure. The findings of this study indicate that the quality of local government financial report disclosure is more influenced by governance factors, particularly transparency, accountability, and accessibility of information, than by demographic factors such as population.